The Relationship between Maternal Education Level, Exclusive Breastfeeding and History of Infectious Diseases with the Incident of Stunting in Toddlers - Ai Nurizkiawati; Muhammad Sahlaini Rahman; Anwar, Rosihan (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2024)
Stunting is a problem of chronic malnutrition caused by insufficient nutritional intake over a long period of time due to intake that is not in accordance with nutritional needs. Stunting can occur from the fetus in the womb and only appears when the child is two years old. Nutritional status not only describes the problem of deficiencies in certain nutrients, but is also related to the level of health and chronic diseases a person has. This research aims to determine the relationship between maternal education, exclusive breastfeeding and a history of infectious diseases with the incidence of stunting in toddlers in the working area of the Teluk Tiram Community Health Center, Banjarmasin. This type of analytical observational research with a cross sectional design. The population in this study were all mothers of toddlers in Teluk Tiram Village, totaling 770 toddlers. Samples were taken using accidental sampling of 20 people. Primary data in the form of respondent characteristics, mother's education level, exclusive breastfeeding and history of infectious diseases were obtained through interviews using questionnaires and nutritional status was obtained by anthropometric measurements (PB/U or TB/U). Data analysis using the Spearman's rho test. The results of research using the Spearman's rho test showed that there was no relationship between maternal education and the incidence of stunting (p=0.652), there was no relationship between exclusive breastfeeding and the incidence of stunting (p=0.126) and there was no relationship between a history of infectious diseases. with the incidence of stunting (p=0.643).